Mechanistic Approach on Melatonin-Induced Hormesis of Photosystem II Function in the Medicinal Plant Mentha spicata - Moustakas, Michael; Sperdouli, Ilektra; Adamakis, Ioannis-Dimosthenis S.; Sas, Begüm; İŞGÖREN, SUMRUNAZ; Moustaka, Julietta; Morales, Fermin (MDPI, 2023)
Melatonin (MT) is considered a new plant hormone having a universal distribution from prokaryotic bacteria to higher plants. It has been characterized as an antistress molecule playing a positive role in the acclimation of plants to stress conditions, but its impact on plants under non-stressed conditions is not well understood. In the current research, we evaluated the impact of MT application (10 and 100 mu M) on photosystem II (PSII) function, reactive oxygen species (ROS) generation, and chlorophyll content on mint (Mentha spicata L.) plants in order to elucidate the molecular mechanism of MT action on the photosynthetic electron transport process that under non-stressed conditions is still unclear. Seventy-two hours after the foliar spray of mint plants with 100 mu M MT, the improved chlorophyll content imported a higher amount of light energy capture, which caused a 6% increase in the quantum yield of PSII photochemistry (Phi(PSII)) and electron transport rate (ETR). Nevertheless, the spray with 100 mu M MT reduced the efficiency of the oxygen-evolving complex (OEC), causing donor-side photoinhibition, with a simultaneous slight increase in ROS. Even so, the application of 100 mu M MT decreased the excess excitation energy at PSII implying superior PSII efficiency. The decreased excitation pressure at PSII, after 100 mu M MT foliar spray, suggests that MT induced stomatal closure through ROS production. The response of Phi(PSII) to MT spray corresponds to a J-shaped hormetic curve, with Phi(PSII) enhancement by 100 mu M MT. It is suggested that the hormetic stimulation of PSII functionality was triggered by the non-photochemical quenching (NPQ) mechanism that stimulated ROS production, which enhanced the photosynthetic function. It is concluded that MT molecules can be used under both stress and non-stressed conditions as photosynthetic biostimulants for enhancing crop yields.
Keywords: Chlorophyll Content; Reactive Oxygen Species; Electron Transport Rate; Non-photochemical Quenching; PSII Photochemistry; Reaction Centers; Excitation Pressure; Stomatal Closure; Excess Excitation Energy